Penentuan Sektor Ekonomi Unggulan di Kabupaten Banyuwangi - Herman Cahyo Diartho (Trunojoyo University of Madura, 2018)
This research is conducted to determine economic of sector competitive for the 2010-2014 in Banyuwangi district. This study analyzes the economic sectors that can grow rapidly and economic sectors that have high competitiveness as well as determining the economic sectors that are seeded in Banyuwangi. For data analysis used primary data questionnaire and interviews and secondary data from BPS form Banyuwangi district PDRB data from 2010-2014. The analytical method used, among others, shift share analysis, Analytical Hierarchy Procces. The results showed that the information and communication sector is a sector that is able to grow rapidly and agriculture, forestry, and fisheries is a sector that has high competitiveness during the years 2010-2014 in Banyuwangi. And based on the AHP in determining the leading economic sectors, sectors that are seeded in Banyuwangi is a wholesale and retail trade sector; repair of cars and motorcycles.